2022
DOI: 10.1016/j.jinf.2022.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term ambient particulate matter exposure on the risk of severe COVID-19

Abstract: Objectives : Previous studies have suggested a relationship between outdoor air pollution and the risk of coronavirus disease 2019 (COVID-19). However, there is a lack of data related to the severity of disease, especially in China. This study aimed to explore the association between short-term exposure to outdoor particulate matter (PM) and the risk of severe COVID-19. Methods : We recruited patients diagnosed with COVID-19 during a recent large-scale outbreak in easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…This study also found that the association remained when controlling for another air pollutant, NO2. Similarly, Li et al (29) found a positive association between PM2.5 and clinically-defined severe COVID-19 across four different lag periods (0-7 days to 0-28 days), which attenuated but remained mostly significant when adjusting for other air pollutants.…”
Section: Pm25 Exposure and Covid-19 Severitymentioning
confidence: 80%
See 3 more Smart Citations
“…This study also found that the association remained when controlling for another air pollutant, NO2. Similarly, Li et al (29) found a positive association between PM2.5 and clinically-defined severe COVID-19 across four different lag periods (0-7 days to 0-28 days), which attenuated but remained mostly significant when adjusting for other air pollutants.…”
Section: Pm25 Exposure and Covid-19 Severitymentioning
confidence: 80%
“…Three of the seven infection studies only included participants with a COVID-19 test (24,31,33), while the remainder either used entire cohorts regardless of whether there was a record of a COVID-19 test (32,34) or conducted analyses of the entire cohort as well as just those tested (16,28). Similarly, all but one study examining severity (28) and mortality (27) were limited to cohorts who were diagnosed with COVID-19, while three were restricted to patients hospitalised with COVID-19 (17,23,29). Restricted cohorts present a risk of collider bias, as PM 2.5 exposure could influence both whether an individual sought testing for COVID-19 or was COVID-19 positive, resulting in distorted associations (35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… ( Chen et al., 2022a ) Jiangsu province, China PM 2.5 , PM 10 Increased risk of severe COVID-19 with OR of 3.99 (1.93-8.25) and 1.82 (1.35-2.44) was associated with a unit increase in PM 2.5 and PM 10 . ( Li et al., 2022 ) Varese, Italy PM 2.5 , PM 10 , NO 2 , NO A unit increase in PM 2.5 was associated with a 5.1% (2.7%-7.5%) increase in COVID-19 cases. Similar findings were observed for PM 10 , NO 2 and NO.…”
Section: Discussionmentioning
confidence: 97%